Hello!
Step 1: Simplify both sides of the equation.<span><span><span>
1.5<span>(<span>x+4</span>)</span></span>−3</span>=<span>4.5<span>(<span>x−2</span>)</span></span></span><span><span><span><span><span><span>
(1.5)</span><span>(x)</span></span>+<span><span>(1.5)</span><span>(4)</span></span></span>+</span>−3</span>=<span><span><span>(4.5)</span><span>(x)</span></span>+<span><span>(4.5)</span><span>(<span>−2</span>)</span></span></span></span>(Distribute)<span><span><span><span><span>
1.5x</span>+6</span>+</span>−3</span>=<span><span><span>4.5x</span>+</span>−9</span></span><span><span><span>
(<span>1.5x</span>)</span>+<span>(<span>6+<span>−3</span></span>)</span></span>=<span><span>4.5x</span>−9</span></span>(Combine Like Terms)<span><span><span>
1.5x</span>+3</span>=<span><span>4.5x</span>−9</span></span><span><span><span>
</span></span></span>Step 2: Subtract 4.5x from both sides.<span><span><span><span>
1.5x</span>+3</span>−<span>4.5x</span></span>=<span><span><span>4.5x</span>−9</span>−<span>4.5x</span></span></span><span><span><span>
−<span>3x</span></span>+3</span>=<span>−9</span></span>
Step 3: Subtract 3 from both sides.<span><span><span><span>
−<span>3x</span></span>+3</span>−3</span>=<span><span>−9</span>−3</span></span><span><span>
−<span>3x</span></span>=<span>−12</span></span>
Step 4: Divide both sides by -3.<span><span><span>
−<span>3x</span></span><span>−3</span></span>=<span><span>−12</span><span>−3</span></span></span><span>
x=<span>4
Hope this helps! Cheerio, and have a lovely day!</span></span>
Volume is legnth times widht times height
lenght=2x-1
width=x-2
height=x+1
multiply all together
use mass distributive property
distributive=a(b+c)=ab+ac so extending that
(a+c)(c+c)=(a+b)(c)+(a+b)(d) then keep distributing so
(2x-1)(x-2)(x+1)
do each one seperately
do the first two first and put the other one (x+1) to the side for later
(2x-1)(x-2)=(2x-1)(x)+(2x-1)(-2)=(2x^2-x)+(-4x+2)=2x^2-5x+2
then do the other one
(x+1)(2x^2-5x+2)=(x)(2x^2-5x+2)+(1)(2x^2-5x+2)=(2x^3-5x^2+2x)+(2x^2-5x+2)=2x^3-3x^2-3x+2
the lasst form is 2x^3-3x^2-3x+2
Answer:
In mathematics, a theorem is a non-self-evident statement that has been proven to be true, either on the basis of generally accepted statements such as axioms or on the basis of previously established statements such as other theorems. A theorem is hence a logical consequence of the axioms, with a proof of the theorem being a logical argument which establishes its truth through the inference rules of a deductive system. As a result, the proof of a theorem is often interpreted as justification of the truth of the theorem statement. In light of the requirement that theorems be proved, the concept of a theorem is fundamentally deductive, in contrast to the notion of a scientific law, which is experimental.
Step-by-step explanation:
Answer:
The answer would be B.
Step-by-step explanation: It is this answer because if it asks you 1 to 5, that means it is one, and then to 5.
Hope this answer helps!
Answer:
The answer is a _10×+8y=15